Assessment of ground water quality of lahar block, Bhind district in Madhya Pradesh - kant, Shashi; Singh, Y.V.; Jat, Lokesh Kumar; Meena, R.; Singh, S.N. (International Journal of Advanced Geosciences, 2015)
In sustainable groundwater study, it is necessary to assess the quality of groundwater in terms of irrigation purposes. The present study attempts to assess the groundwater quality through Irrigation Water Quality Index (IWQI) in hard-rock aquifer system and sustainable water use in Lahar block, Bhind of district, Madhya Pradesh, India. The quality of ground water in major part of the study area is generally good. In order to understand the shallow groundwater quality, the water samples were collected from 40 tube wells irrigation water. The primary physical and chemical parameters like potential Hydrogen (pH), Total Dissolved Solids (TDS), calcium (Ca2+), magnesium (Mg2+), sodium (Na+), potassium (K+), bicarbonate (HCO3-), carbonate (CO32-), chloride (Cl-), and nitrate (NO3-) were analyzed for (irrigation water quality index ) IWQI. The secondary parameters of irrigation groundwater quality indices such as Sodium Adsorption Ratio (SAR), Sodium Soluble Percentage (SSP), Residual Sodium Carbonate (RSC), Permeability Index (PI), and Kellies Ratio (KR) were also derived from the primary parameter for irrigation water quality index (IWQI). The IWQI was classified into excellent to unfit condition of groundwater quality based on their Water Quality Index (WQI). The IWQI (82.5%+15.0%) indicate that slightly unsustainable to good quality of ground water. Due to this quality deterioration of shallow aquifer, an immediate attestation requires for sustainable development.